Tensile strength and early healing of self‐locking and surgeon's knots. Issue 8 (11th August 2020) - Weatherall, Kathleen M.; Boone, Lindsey H.; Caldwell, Fred J.; Cole, Robert C.; Cattley, Russell C.; Lascola, Kara M.; Clark‐Price, Stuart C.; Farag, Ramsis; Perkins, Edmon; Hanson, R. Reid
Abstract: Objective: To compare the biomechanical properties and healing of ventral midline celiotomies (VMC) closed with a self‐locking knot combination and forwarder start and Aberdeen end (F‐A) vs a traditional knot combination and surgeon's start and end (S‐S). Study design: In vivo, experimental. Animals: Twenty‐one horses. Methods: Fourteen horses underwent VMC, which was closed with either an F‐A (n = 7) or an S‐S (n = 7) knot combination. Incisions were subjectively graded by masked evaluators for dehiscence, edema, and drainage. Biomechanical testing was performed on three abdominal segments, and histology was performed on one segment from each animal after humane euthanasia 10 days post‐VMC. The abdominal wall of control horses (n = 7, no celiotomy) was collected for biomechanical testing. Results: Forwarder start and Aberdeen end and S‐S horses had less tensile strength compared with control horses ( P  ≤ .001). No differences were detected between treatment groups for any variable evaluated, including tensile strength ( P = .975), location of failure ( P = .240), and histologic healing at the knot ( P = .600). Conclusion: Closure of VMC with self‐locking knots resulted in biomechanical and healing features similar to those with a traditional closure technique, with neither restoring the tensile strength of the linea alba. Clinical significance: Results of this study provide evidence to support a clinical trial to evaluate long‐term performance of the F‐A self‐locking knot closure in horses.